Kebijakan Tata Kelola Pelaksanaan Makan Bergizi Gratis Terhadap Kelayakan Implementasi Berkelanjutan Yang Berdampak Secara Multiplier Effect Dengan Pemanfaatan Teknologi - Diding Bajuri; Nurul Jannah Lailatul Fitria; Sigit Sugiarto; Elih Solehah Fatimah; Elawati (Universitas Majalengka, 2026)
Free Nutritious Meal (MBG) program is a strategic government policy aimed at improving students’ nutritional quality and supporting human resource development toward Indonesia Emas 2045. In addition to fulfilling nutritional needs, the MBG program also has the potential to create a multiplier effect on the local economy through the involvement of MSMEs, local farmers, and food distribution providers. However, the implementation of the program still faces several challenges related to governance, sustainability, inter-institutional coordination, and the utilization of technology. This study aims to analyze the governance of the MBG program toward the feasibility of sustainable implementation that generates a multiplier effect through technology utilization. This research employed a mixed methods approach with a Sequential Explanatory design. Data were collected through questionnaires, interviews, observations, and documentation. Quantitative data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM), while qualitative data were analyzed using narrative analysis techniques. The results indicate that governance plays an important role in supporting sustainable implementation, strengthening stakeholder coordination, and enhancing local economic impacts. Furthermore, technology utilization contributes to improving transparency, monitoring, and accountability in program implementation.